VALIDITAS DAN RISIKO PEMBUKTIAN TANDA TANGAN ELEKTRONIK DALAM PERJANJIAN PERDATA DI INDONESIA - Ulya Ardhia Cahyani Ahmad (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
This study examines the validity of electronic signatures (e-signatures) and the challenges in proving their authenticity in civil contracts in Indonesia. Based on an analysis of Law No. 11 of 2008 on Electronic Information and Transactions (UU ITE) as amended by Law No. 19 of 2016, as well as Government Regulation No. 71 of 2019, e-signatures have the same legal force as conventional signatures if certain requirements are met, particularly regarding identity authentication, information integrity, and non-repudiation. The findings reveal different approaches in practice: the formalist view emphasizes official certification, the flexible view accepts uncertified e-signatures as long as their authenticity can be proven, and the protective view restricts their use to high-value transactions. An analysis of several court decisions shows patterns in the acceptance of e-signatures: (1) certified e-signatures tend to be fully accepted, (2) uncertified e-signatures are accepted to a limited extent if supported by technical evidence such as server logs and expert testimony, and (3) there are still weaknesses in regulations, infrastructure, and the legal apparatus’s understanding of e-signature technology. Proof-related risks include document security vulnerabilities, difficulties in accessing log data, and a lack of technological literacy among legal practitioners. Keywords: Electronic Signature, Legal Validity